External and macroeconomic adjustment in the larger euro area countries - Elena Angelini; Michele Ca' Zorzi; Katrin Forster (European Central Bank (ECB), 2014)
A balanced current account in the euro area has disguised sizeable net lending imbalances at the country level, exposing the common currency area to severe pressures during the financial crisis. The key contribution of this paper is to evaluate the adjustment process through the lenses of the New Multi Country Model at the country and sectoral level. We find that shocks to the external, fiscal and monetary environment help explain, to a large degree, the sizeable current account adjustment and rise in unemployment in Spain. The model also suggests that a recovery in wage competitiveness helps to reduce external deficits at the cost of higher net borrowing by households. The stimulus effects on aggregate demand, via the interest rate response of the common monetary authority and the competitiveness channel, are present but not overly large, as the rebound in economic activity depends mainly on global demand, supportive monetary policy, business and consumer confidence.
Keywords: C5; F32; F41; O52; 330; current account; euro area countries; modeling; net lending